Pengaruh Worklife Balance dan Budaya Organisasi terhadap Work Engagement dengan Kepuasan Kerja Sebagai Variabel Mediasi pada Personel Satuan Reserse Kriminal Polres Sinjunjung - Andri. A; Almasdi, Almasdi (CV. ALIM'SPUBLISHING, 2026)
This study is motivated by the importance of human resource management within police institutions, particularly in enhancing personnel work engagement through work-life balance and organizational culture. Personnel in the Criminal Investigation Unit of the Sijunjung Police face various challenges, such as heavy workloads, job stress, limited time with family, and an organizational culture that remains hierarchical. These conditions have the potential to affect personnel’s job satisfaction and work engagement in performing their duties. This study aims to analyze the influence of Work-Life Balance and Organizational Culture on Work Engagement, with Job Satisfaction as a mediating variable, among personnel of the Criminal Investigation Unit of the Sijunjung Police Department. The background of this study stems from the importance of work engagement within a police environment characterized by high task loads and complex professional pressures. The research method employed a quantitative approach using a census technique on 36 respondents, and data analysis was conducted using Partial Least Squares (PLS) via SmartPLS 3.0 software.The results of the study indicate that work-life balance has a significant effect on job satisfaction, albeit with a negative relationship, while organizational culture does not have a significant effect on either job satisfaction or work engagement. Furthermore, job satisfaction does not have a significant effect on work engagement and does not mediate the relationship between the main variables. In conclusion, increasing employee work engagement requires a more comprehensive approach through the strengthening of motivational factors, psychological support, and participatory leadership so that optimal well-being and performance can be achieved.